2021
DOI: 10.1002/pon.5661
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and its associated factors in brain tumor patients in Karachi, Pakistan: An analytical cross‐sectional study

Abstract: Objectives This study assessed resilience in brain tumor patients at a tertiary care hospital in Pakistan (a lower middle‐income country; LMIC) and explored its relationship with patients' sociodemographic factors, clinical characteristics, social support, and mental health. Methods A cross‐sectional survey was conducted amongst adult (≥18 years) patients with brain tumor at the Aga Khan University Hospital, Pakistan. Resilience was assessed by Wagnild and Young's Resilience Scale, and patients' psychosocial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…In addition, all symptom components on the QLQ-BN20 were lower in our study, barring weakness of legs (mean of 18.40 ± 25.33 in our study vs. weighted mean 17.72 ± 92.99) [25]. It is possible that these ndings of an overall better QoL in our sample are a function of the higher resilience and social support, and lower depression and anxiety, which contribute towards better QoL [21]. The higher social support, in turn, is likely due to the close-knit extended family systems that are a feature of South Asian households (54% of patients in our study lived in extended families).…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…In addition, all symptom components on the QLQ-BN20 were lower in our study, barring weakness of legs (mean of 18.40 ± 25.33 in our study vs. weighted mean 17.72 ± 92.99) [25]. It is possible that these ndings of an overall better QoL in our sample are a function of the higher resilience and social support, and lower depression and anxiety, which contribute towards better QoL [21]. The higher social support, in turn, is likely due to the close-knit extended family systems that are a feature of South Asian households (54% of patients in our study lived in extended families).…”
Section: Discussionmentioning
confidence: 46%
“…The higher the score on the RS-14, the higher the resilience. The Urdu version has been validated previously [21] and demonstrated excellent internal consistency in the current population as well (Cronbach's alpha of 0.903).…”
Section: Data Collection Toolsmentioning
confidence: 91%
See 1 more Smart Citation
“…The guide was developed by the research team based on a comprehensive review of the literature, and an existing conceptual framework of resilience underpinning Wagnild and Young's Resilience Scale [44,45]. This resilience scale is frequently used in studies about the resilience conducted in Pakistan, and the scale has been validated for use among Pakistani married women [53][54][55][56][57][58]. The principal investigator (PI) of the current study performed this validation while carefully taken into consideration the content and cultural biases [44] which measures the following five attributes that strengthen an individual's capacity for resilience: 1): an understanding of the meaning of life; 2) perseverance/determination; 3) existential aloneness/friendship with self; 4) equanimity and 5) selfreliance.…”
Section: Interview Guidementioning
confidence: 99%
“…In this paper, distress refers to the experience of emotional strain. Various studies have shown a correlation between distress and cancer [ 3 , 4 , 5 , 6 ]. Because approximately one-third of all patients with cancer suffer from distress that requires psycho-oncological treatment [ 7 , 8 , 9 , 10 ], it is important to investigate factors of their distress in order to be able to offer them targeted help.…”
Section: Introductionmentioning
confidence: 99%